Case Report: Cardiac Surgery and Combined Lipid-Lowering Drug Therapy for Homozygous Familial Hypercholesterolemia - Gao, Mingxin; Yu, Wenyuan; Hu, Hui; Liu, Hongli; Fan, Kangjun; Gu, Chengxiong; Wang, Lvya; Yu, Yang (Frontiers in Pediatrics, 2020)
Homozygous familial hypercholesterolemia (HoFH) is a rare, autosomal dominant, hereditary, metabolic disease. HoFH patients exhibit severe coronary stenosis and valvular disease, which may result in sudden death, even during adolescence. The challenges faced during surgery and the poor curative effect of conventional lipid-lowering therapy create a treatment bottleneck. We report a rare case of HoFH in a 12-year-old boy with acute myocardial infarction, severe mitral insufficiency, and moderate aortic insufficiency. Coronary artery bypass grafting and valvuloplasty resulted in improved heart function. Postoperative combined lipid-lowering drug therapy was able to reduce low-density lipoprotein cholesterol level from 15.37 mm/L to 6.41 mmol/L. Thus, the combination of medical and surgical treatment was considered effective and can be used to inform treatment guidelines for HoFH with severe complications.